First-Line Systemic Treatment Strategies for Unresectable Hepatocellular Carcinoma: A Systematic Review and Network Meta-Analysis of Randomized Clinical Trials - Liu, Wenfeng; Quan, Bing; Lu, Shenxin; Tang, Bei; Li, Miao; Chen, Rongxin; Ren, Zhenggang; Yin, Xin (Frontiers in Oncology, 2021)
Objective: Several new first-line treatments were recently approved for unresectable hepatocellular carcinoma (HCC). In this meta-analysis, we compare the efficacy and safety of first-line systemic treatments to provide information for clinical decision making in unresectable HCC. Methods: Pubmed, Science Direct, Web of Science, Scopus, Ovid MEDLINE, Embase, Google Scholar, the Cochrane Library, EMbase, CNKI, CBM, VIP, and the Wanfang databases, as well as the Cochrane Central Register of Controlled Trails were searched for randomized clinical trials evaluating the efficacy of first-line chemotherapy, molecular targeted therapy, or immunotherapy for unresectable HCC. Hazard ratios with 95% confidence intervals (CIs) were calculated to explore the effects of various treatment options on overall survival (OS) and progression-free survival (PFS), whereas odd ratios with 95% CIs were used for adverse events (AEs) and serious adverse events (SAEs). A network meta-analysis was performed to synthesize data and for direct and indirect comparisons between treatments. The cumulative ranking curve (SUCRA) and P score were used to rank treatments. The risk of bias across studies was assessed graphically and numerically using the funnel plot and Egger’s regression test. Results: Fifteen studies including 9005 patients were analyzed. Sintilimab plus bevacizumab, atezolizumab plus bevacizumab, and donafenib had better OS outcomes than sorafenib. Sintilimab plus bevacizumab, atezolizumab plus bevacizumab, lenvatinib, and linifanib had better PFS outcomes than sorafenib. The results of network meta-analysis showed that sintilimab plus bevacizumab was associated with the best OS and PFS. Egger’s tests indicated that none of the included studies had obvious publication deviation. Conclusion: Sintilimab plus bevacizumab showed the best OS and PFS outcomes with no additional AEs or SAEs. Thus, sintilimab plus bevacizumab may be a better first line choice for the treatment of patients with unresectable HCC. Key words: unresectable hepatocellular carcinoma; network meta-analysis; first line systemic therapy; randomized clinical trials; systematic review